IMPLEMENTATION OF OPEN BROADCASTER SOFTWARE STUDIO IN MUSIC PERFORMANCE MANAGEMENT THROUGH LIVE STREAMING - Danny Ivanno Ritonga; Tri Danu Satria; Aqsa Mulya (Gondang: Jurnal Seni dan Budaya, 2021)
This study aims to compile the management of performing arts in musical performances through live streaming at the Music Education Study Program, State University of Medan and to develop methods for implementing Open Broadcaster Software Studio in musical performances through live streaming in the Music Education Study Program. This study uses a qualitative approach by following the opinions of Miles and Huberman, namely (1) data collection, which is carried out through interviews, observations, document digests, recording and recording; (2) data reduction, which is done by summarizing, selecting the main things, focusing on the important things, looking for themes and patterns and discarding unnecessary ones; (3) data display, which is done by showing data and presenting it in the form of narrative text and charts; (4) conclusion drawing/verification conducted by drawing conclusions and verifying the research findings. The results of the study indicate that the management of performing arts in Karya Musik performances through Live Streaming starts from the planning, organizing, actualling, and controlling stages. A show can be managed well if it has a good management system too. By having a good management system, the performance of the musical works will be able to achieve greater goals, targets, or outputs. Planning begins with preparing Human Resources and preparing hardware and software. The organization consists of the Program Director as the person in charge, Production manager who oversees the Floor Director and Talent/musicians, Multimedia manager who oversees IT operators, Software and Hardware Operators, and Camera Man, and Stage Manager who oversees Sound Operators and Lighting Operators. The implementation of Musical Performances through Live Streaming has been carried out 3 times. They are the Nusantara Tetabuhan Music Show, the Langkat Tamiang Rentak Show, and also the Orchestra Music Show. the methods and steps taken in implementing the OBS Studio software as a medium for the virtual musical performance process include input and output methods and using OBS Studio Software. The Method of Performing Live Streaming Music Works using OBS Studio Software begins with determining the settings and design layout, selecting Capture Card, Copy Code Live Streaming on Youtube, Paste Code Live Streaming to the OBS system, and Start Streaming.